Structuring methodology of the Computerized Nursing Process in Emergency Care Units - Fernanda Paese; Grace Teresinha Marcon Dal Sasso; Gabriela Winter Colla
ABSTRACT Objective: To structure the Computerized Nursing Process using the International Classification for Nursing Practice (ICNP®) version 2.0 to emergency care units in a computerized structure. Method: This is a methodological and technological research that followed the stages: (1) establishment of the development team and resources; (2) adequacy of clinical situations, diagnoses and nursing interventions for the emergency area; (3) association of diagnoses and interventions based on ICNP®; (4) organization and codification of clinical evaluation, diagnoses and nursing interventions; (5) transfer of data to the a computerized platform. Results: Readjustment and construction of 1,445 possibilities of clinical evaluations associated with 961 different diagnoses and their corresponding interventions to the most frequent situations in emergency services. Conclusion: ICNP® has a strong and solid form for the development of the computerized nursing process able to support nurses in safe decision-making to improve the quality of health care.